Tuning the charge carrier mobility in few-layer PtSe2 films by Se : Pt ratio. Issue 44 (10th August 2021) - Hrdá, Jana; Tašková, Valéria; Vojteková, Tatiana; Slušná, Lenka Pribusová; Dobročka, Edmund; Píš, Igor; Bondino, Federica; Hulman, Martin; Sojková, Michaela
Abstract : This work presents the fabrication of horizontally aligned PtSe2 films using one-zone selenization of pre-deposited platinum layers. We have identified the Se : Pt ratio as a parameter controlling the charge carrier mobility in the thin films. Abstract : Recently, few-layer PtSe2 films have attracted significant attention due to their properties and promising applications in high-speed electronics, spintronics and optoelectronics. Until now, the transport properties of this material have not reached the theoretically predicted values, especially with regard to carrier mobility. In addition, it is not yet known which growth parameters (if any) can experimentally affect the carrier mobility value. This work presents the fabrication of horizontally aligned PtSe2 films using one-zone selenization of pre-deposited platinum layers. We have identified the Se : Pt ratio as a parameter controlling the charge carrier mobility in the thin films. The mobility increases more than twice as the ratio changes in a narrow interval around a value of 2. A simultaneous reduction of the carrier concentration suggests that ionized impurity scattering is responsible for the observed mobility behaviour. This significant finding may help to better understand the transport properties of few-layer PtSe2 films.